Value-Based Leadership in the Management of Educational Institutions Course: A Case Study of Improving the Quality and Relevance of the Program - Rastiti, Disma Ajeng (Universitas Negeri Semarang, 2025)
This research examines the implementation of value-based leadership in the management of course education institutions (LPK) and its impact on improving the quality and relevance of programs. Using a qualitative approach with case study design on five LPKs in Central Java, the research explores the application of integrity, innovation, and social benefit values in institutional management aspects. Data collection was carried out through method triangulation including in-depth interviews, participatory observation, and documentation study. The results show that the implementation of integrity values is manifested in transparency and accountability in resource management and the development of a systematic quality assurance system. Innovation values are implemented through adaptive curriculum development, varied learning methods, and technology utilization in service quality improvement. Social benefit values are actualized in socially impactful programs, strategies for reaching marginalized groups, and programs relevant to local community needs. The research produces a value-based leadership model that includes stages of value articulation, internalization, policy development, program implementation, and continuous evaluation and improvement. This model has implications for the balance between business objectives and social responsibility, as well as improving the quality and relevance of LPK programs in the context of the dynamics of labor market needs and technological developments.